EFFEKTIVITAS INTERVENSI BACK MASSAGE TERHADAP PENURUNAN ANXIETY PADA PASIEN CONGESTIVE HEARTFAILURE (CHF) : A SYSTEMATIC REVIEW - Valentino Febryandy; Riska Fadilah (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Background: Congestive Heart Failure (CHF) is a clinical syndrome caused by functional or structural heart abnormalities that interfere with ventricular filling or ejection of blood into the systemic circulation. Objective: To determine the effectiveness of back massage intervention in reducing anxiety in Congestive Heart Failure (CHF) patients. Physiologically, back massage is a relaxation technique that affects the body physically and psychologically. Back massage provides a relaxing effect by stimulating the release of endorphins in the brain which have the effect of suppressing sympathetic nerve activity and stimulating parasympathetic nerve activation. Method: This type of study is a systematic review, a strategy for searching articles using the PICOS framework. Inclusion criteria: Articles from 2013 to 2023; Not pay; Full text; In English language. The literature search in this systematic review was carried out through three databases of medium to high reputation, including ProQuest, Cochrane and PubMed. Results: There were Selecting the title, abstract and keywords for the articles resulted in only 52 articles that matched the title, abstract and keywords of the article with the researcher's theme. The next stage was reading the entire text of the articles that met the inclusion criteria, totaling 9 articles, then assessing the quality of the articles and the risk of bias using the JBI critical appraisal tools, namely an assessment based on research studies. So only 4 articles were assessed using JBI critical appraisal. Conclusion: showed that back massage was effective in reducing state anxiety, cortisol levels, blood pressure and HR, as well as improving sleep quality in patient caregivers.